Jachymov: Heaven or Hell?: Contrasting Historical Narratives about Jachymov, Czech Republic and its Radioactive Elements - Wirka, Katherine (My University, 2012)
The small town of Jachymov, Czech Republic is nestled in the Krusne Hory, which is literally translated from Czech to English as the "Cruel Mountains", but known in English as the Ore Mountains. The town is located in the northwest of the country close to the German border. My first journey to Jachymov was for a school-sanctioned trip in 2006. My classmates and I were told that it was a very historically significant town in northern Bohemia; that it was founded as a silver mining town and was the birthplace of the English word "dollar." They also explained that in addition to touring the town's museum, we would meet some survivors of one of the many "concentration camps" that existed in the area in the early days of the Czechoslovak communist regime. This statement piqued my interest, as I had never heard the term concentration camp used in any other context then referring to the Nazi regime's use of them during World War Two. I was eager to learn more about Jachymov, which seemed to be a place ripe with history and intrigue. In the end I made two trips to Jachymov: the aforementioned school sponsored trip in 2006 and a second trip in 2010 to gather research data for this thesis. As both prelude and introduction to my thesis, I offer two impressionistic accounts of these visits.
Includes color photographs, appendix, maps, interview list and bibliography.
Keywords: Jachymov; Czech Republic